Regional modulation of toll-like receptor signaling pathway genes in acute epididymitis in mice - Andrade, Alexandre D. [UNESP]; Almeida, Priscila G. C. [UNESP]; Mariani, Noemia A. P. [UNESP]; Santos, Natalia C. M. [UNESP]; Camargo, Isabela A. [UNESP]; Martini, Poliana V. [UNESP]; Kushima, Helio [UNESP]; Ai, Dingding; Avellar, Maria Christina W.; Meinhardt, Andreas; Pleuger, Christiane; Silva, Erick J. R. [UNESP] (Wiley, 2024)
Background: Region-specific immune environments in the epididymis influence the immune responses to uropathogenic Escherichia coli (UPEC) infection, a relevant cause of epididymitis in men. Toll-like receptors (TLRs) are essential to orchestrate immune responses against bacterial infections. The epididymis displays region-specific inflammatory responses to bacterial-derived TLR agonists, such as lipopolysaccharide (LPS; TLR4 agonist) and lipoteichoic acid (LTA; TLR2/TLR6 agonist), suggesting that TLR-associated signaling pathways could influence the magnitude of inflammatory responses in epididymitis. Objectives: To investigate the expression and regulation of key genes associated with TLR4 and TLR2/TLR6 signaling pathways during epididymitis induced by UPEC, LPS, and LTA in mice. Material and methods: Epididymitis was induced in mice using UPEC, ultrapure LPS, or LTA, injected into the interstitial space of the initial segment or the lumen of the vas deferens close to the cauda epididymidis. Samples were harvested after 1, 5, and 10 days for UPEC-treated animals and 6 and 24 h for LPS-/LTA-treated animals. Ex vivo epididymitis was induced by incubating epididymal regions from naive mice with LPS or LTA. RT-qPCR and Western blot assays were conducted. Results: UPEC infection up-regulated Tlr2, Tlr4, and Tlr6 transcripts and their associated signaling molecules Cd14, Ticam1, and Traf6 in the cauda epididymidis but not in the initial segment. In these epididymal regions, LPS and LTA differentially modulated Tlr2, Tlr4, Tlr6, Cd14, Myd88, Ticam1, Traf3, and Traf6 expression levels. NFKB and AP1 activation was required for LPS- and LTA-induced up-regulation of TLR-associated signaling transcripts in the cauda epididymidis and initial segment, respectively. Conclusion: The dynamic modulation of TLR4 and TLR2/TLR6 signaling pathways gene expression during epididymitis indicates bacterial-derived antigens elicit an increased tissue sensitivity to combat microbial infection in a spatial manner in the epididymis. Differential activation of TLR-associated signaling pathways may contribute to fine-tuning inflammatory responses along the epididymis.
Keywords: AP1; epididymis; immune responses; LPS; LTA; male fertility; NFKB; UPEC